2016
DOI: 10.1097/pcc.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Long-Stay Parents in the ICU: A Qualitative Study of Parent and Staff Perspectives

Abstract: Over time, long-stay families will likely become more familiar with the environment of the ICU, more knowledgeable about their child's medical needs and more familiar with the staff looking after their child. This has a number of implications for staff working in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
(50 reference statements)
0
28
0
1
Order By: Relevance
“…Early in our study, we found that all parents commented that nurses both facilitated and inhibited parental involvement in their infant's physical care; this belief is echoed in the literature regarding parent participation in the PICU (Ames et al, 2011;Cantwell-Bartl and Tibballs, 2013;Geoghegan et al, 2016). As their participation increased, parents began to view themselves as experts in the care of their infant.…”
Section: Participationmentioning
confidence: 53%
See 3 more Smart Citations
“…Early in our study, we found that all parents commented that nurses both facilitated and inhibited parental involvement in their infant's physical care; this belief is echoed in the literature regarding parent participation in the PICU (Ames et al, 2011;Cantwell-Bartl and Tibballs, 2013;Geoghegan et al, 2016). As their participation increased, parents began to view themselves as experts in the care of their infant.…”
Section: Participationmentioning
confidence: 53%
“…Studies of parents whose infants had prolonged hospitalizations reported that parents began their infant's stay in the PICU naïve, but over time came to better understand the unit and its culture. For example, Geoghegan et al (2016) found that parents either developed strong relationships with the staff and came to know the culture of the unit, or became increasingly stressed over time and their "needs and concerns escalated". This finding was true for our prolonged-stay parents as well in that one of the two parent dyads formed a highly functional working relationship with the health care team while the other dyad developed an active distrust of the clinicians and experienced multiple conflicts related to their infant's care.…”
Section: Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…E a participação mais ativa permite uma percepção de que todo o possível está sendo feito. 4 17 Portanto, pode-se afirmar que a qualidade da comunicação entre os profissionais de Enfermagem e a família, por vezes, é deficiente, sendo justificada pela formação profissional mecanicista, com ênfase nos procedimentos, com excesso de atribuições administrativas, no caso do enfermeiro. 10 A discrepância no linguajar dos profissionais e da família causa interferências na comunicação, prejudicando a capacidade desta em participar das decisões terapêuticas propostas para o filho.…”
Section: Discussionunclassified